Between memory and mobilization: the graffiti and street art of the Paris Commune - Smith, M (University of Nebraska Press, 2021)
Discussing his 1971 urban art installation, Les Gisants de la Commune de Paris, Ernest Pignon-Ernest stated he felt it necessary for art dedicated to the Paris Commune to be created in the street. Only there could it do justice to a movement built on popular seizure of urban space. In recent years, as 'street art' has emerged as a significant artistic movement, the affinity Pignon-Ernest asserted between art in the street and the Commune has continued to make itself felt. This article discusses three Paris-based street artists who have referenced the Commune: A2, Morèje, and Rue Meurt d'Art. Their work resists the Commune's erasure from collective memory. However, their strategies sometimes risk relegating it to the past, stripping it of its political radicalism. This, combined with street art's growing commercialization and institutionalization, poses questions about urban art's capacity to engage the Commune on an ideological—not just iconographic—level.